Optimal feedback control for fractional neutral dynamical systems. (4th May 2018) - Liu, Zhenhai; Li, Xuemei; Zeng, Biao
Abstract : In this paper, we consider feedback control systems governed by fractional neutral equations involving Riemann–Liouville derivatives. Firstly, we show the existence and uniqueness of solutions for the feedback control systems by applying Krasnoselskiis fixed point theorem. Then, we use Filippove theorem to obtain the existence of feasible pairs. Finally, an existence result of optimal control pairs for the Lagrange problem is proved.